PENERAPAN MODERASI BERAGAMA DALAM MENANAMKAN SIFAT CINTA AL-QURAN DI TPA IMAM AS-SYAFI’I METRO TIMUR - Dhimas Febryansah; liana dewi susanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Institut Agama Islam Negeri Metro, 2021)
Moderation simply means nothing less or nothing more which means moderate, while religion is a certain teaching that is mandated by someone to be used as a guide for their life. Islam is a religion that has been the perfect companion of previous religions. Islam was revealed to the Prophet Muhamman through the angel Gabriel. In the teaching of islam there is a book that is the source of all sources of law, namely the Al-Qur‟an, therefore as Muslims it is necessary to study the contents of this Qur‟an. Everything that is experienced by Allah‟s human beings is described in the Qur‟an, therefore as Muslims we need to have that our lives are in accordance with the instuctions contaied in the Al- Qur‟an.